Advancing to 4.6 V Review and Prospect in Developing High‐Energy‐Density LiCoO2 Cathode for Lithium‐Ion Batteries. Issue 5 (24th March 2022) - Zhang, Si‐Dong; Qi, Mu‐Yao; Guo, Si‐Jie; Sun, Yong‐Gang; Tan, Xin‐Xin; Ma, Pei‐Zhong; Li, Jin‐Yang; Yuan, Rong‐Zhong; Cao, An‐Min; Wan, Li‐Jun
Abstract: Layered LiCoO2 (LCO) is one of the most important cathodes for portable electronic products at present and in the foreseeable future. It becomes a continuous push to increase the cutoff voltage of LCO so that a higher capacity can be achieved, for example, a capacity of 220 mAh g –1 at 4.6 V compared to 175 mAh g –1 at 4.45 V, which is unfortunately accompanied by severe capacity degradation due to the much‐aggravated side reactions and irreversible phase transitions. Accordingly, strict control on the LCO becomes essential to combat the inherent instability related to the high voltage challenge for their future applications. This review begins with a discussion on the relationship between the crystal structures and electrochemical properties of LCO as well as the failure mechanisms at 4.6 V. Then, recent advances in control strategies for 4.6 V LCO are summarized with focus on both bulk structure and surface properties. One closes this review by presenting the outlook for future efforts on LCO‐based lithium ion batteries (LIBs). It is hoped that this work can draw a clear map on the research status of 4.6 V LCO, and also shed light on the future directions of materials design for high energy LIBs. Abstract : It becomes a continuous push to increase the cutoff voltage of LiCoO2 to reach 4.6 V so that a higher capacity can be achieved. However, severe structural degradation is originated in both surface and bulk for 4.6 V LiCoO2 . In order to improve the cyclic stability, different strategies are considered to address the challenges related to its high voltage applications.